2015
DOI: 10.1002/cam4.375
|View full text |Cite
|
Sign up to set email alerts
|

Differences in IGF‐axis protein expression and survival among multiethnic breast cancer patients

Abstract: There is limited knowledge about the biological basis of racial/ethnic disparities in breast cancer outcomes. Aberrations in IGF signaling induced by obesity and other factors may contribute to these disparities. This study examines the expression profiles of the insulin-like growth factor (IGF)-axis proteins and the association with breast cancer survival across a multiethnic population. We examined the expression profiles of the IGF1, IGF1R, IGFBP2 (IGF-binding proteins), and IGFBP3 proteins in breast tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“… 34 In addition, IGFBP2 was found to be a predictor of recurrence-free survival (RFS) when measured along with four other proteins in TNBC patients receiving post-neoadjuvant chemotherapy. 60 However, a report by Hernandez et al 61 in 2015 disagreed with the findings. Hernandez et al examined the relationship between IGF and IGFBP expression with survival rates in Asian, Pacific Islander, and Caucasian patients and found that increased IGFBP2 expression correlated to a decreased breast cancer survival rate, and the increased IGFBP2 expression varied between racial/ethnic groups.…”
Section: Tnbc Biomarkers On the Cell Surface Membranementioning
confidence: 91%
“… 34 In addition, IGFBP2 was found to be a predictor of recurrence-free survival (RFS) when measured along with four other proteins in TNBC patients receiving post-neoadjuvant chemotherapy. 60 However, a report by Hernandez et al 61 in 2015 disagreed with the findings. Hernandez et al examined the relationship between IGF and IGFBP expression with survival rates in Asian, Pacific Islander, and Caucasian patients and found that increased IGFBP2 expression correlated to a decreased breast cancer survival rate, and the increased IGFBP2 expression varied between racial/ethnic groups.…”
Section: Tnbc Biomarkers On the Cell Surface Membranementioning
confidence: 91%
“…It is likely that, in addition to a variety of social, structural, and environmental factors, biological factors influence how breast cancer is expressed ( Coughlin & Cypel, 2013 ). Alterations in IGF signaling induced by obesity and/or other factors may lead to these disparities ( Hernandez et al, 2015 ). However, there is currently a paucity of health intervention studies that include sizeable numbers of African American or Hispanic breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R positivity reflects a well-differentiated tumor with low metastatic tendency ( Aaltonen et al, 2014 ). Among women with triple-negative breast cancers, IGF-1R is a predictor of poorer survival ( Hernandez et al, 2015 ). Hernandez et al (2015) examined the expression of proteins in the IGF axis and the association with breast cancer survival.…”
Section: Insulin-like Growth Factor and Its Binding Proteins And Rmentioning
confidence: 99%
See 2 more Smart Citations